Economic Challenges and Pathways in the Visegrad Countries: Growth and Sustainability - Portrusching, Tamás; Szalai, Szilvia Módosné; Poyda-Nosyk, Nina; Lakshmi, Vasantha Patibandla; Malatyinszki, Szilárd; Dávid, Lóránt Dénes (Journal of Ecohumanism, 2024)
The economic development of the Visegrad countries (V4)—the Czech Republic, Hungary, Slovakia, and Poland—offers valuable insights into the complexities of regional competition and collaboration in Central and Eastern Europe. This study investigates key economic indicators, including GDP performance, trade dynamics, and labor market trends, to assess the region's developmental trajectory over recent decades. Particular attention is given to Hungary’s comparative position, highlighting its strengths, weaknesses, and long-term growth potential within the V4 framework. The research explores how historical, political, and economic transitions, such as European Union accession and structural reforms, have shaped the region's economic landscape, revealing both opportunities and persistent disparities among the V4 nations. A pivotal focus of this study is the integration of circular economy principles, such as resource efficiency, waste reduction, and sustainable innovation, into regional and national policies. These principles, increasingly prioritized by the European Union, have the potential to address critical environmental challenges while fostering economic resilience. By adopting circular economy practices, V4 countries can enhance competitiveness, attract sustainable investments, and achieve long-term economic stability. The findings emphasize that circular economy strategies not only align with global sustainability goals but also support regional objectives by optimizing trade efficiency, reducing dependency on non-renewable resources, and strengthening industrial competitiveness. Moreover, the study identifies key challenges facing the V4 economies, including labor market disparities, productivity gaps, and uneven regional development, particularly between urbanized and peripheral areas. Quantitative analysis reveals that countries adopting coordinated policies and leveraging EU resources effectively are better positioned to mitigate these challenges and maintain sustainable economic growth. By drawing comparisons across the V4 countries, this research provides actionable insights for policymakers, scholars, and stakeholders seeking to balance economic growth with environmental sustainability, thereby enhancing the region's integration into global markets. The study underscores the critical need for a holistic approach that integrates circular economy principles, technological advancements, and cross-border cooperation to achieve shared developmental goals.